Fund Ownership of Sharia Banking According to Islamic Economic Political Perspective - Muhamad Izazi Nurjaman (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
The concept of ownership in Islamic economics states that individuals or legal entities that have the right to ownership of a property may use it freely as long as it does not violate Islamic economic principles and the public interest. However, for Islamic banking, the ownership of funds used as business capital comes from investor customers who deposit their funds in Islamic banks. This has an effect on the ownership status of these funds. This article uses a descriptive literature research method taken from various factual references with a focus on using a normative juridical approach. This type of research is qualitative research using data analysis through several steps such as focusing data, presenting funds and drawing conclusions. The results of this study reveal the fact that the ownership rights of funds in Islamic banking are sourced from the first party funds as the bank's founder, the second party funds as shareholders and third party funds as investor customers. Ownership of these funds cannot be separated from the contract mechanism used. So that the contract used is the cause of Islamic banks having ownership rights to use these assets for business activities. The use of these funds is guaranteed by law, which shows the role of Islamic economic politics through the legal umbrella that regulates the operational system of Islamic banking, especially in the permitting of the use of investor funds for business activities through the mechanism of channeling funds and service mechanisms.